Police powers in the enforcement of Islamic criminal law - Ab Aziz, Shamrahayu (LexisNexis, 2010)
Royal Malaysian Police is the major law enforcement agency in the country. The prime duty of the police force is to maintain the law and order of the country. This short essay seeks to discuss the police power regarding the enforcement of Islamic criminal law. The police power on the subject has been a subject of discussion among the masses and sometimes, it is also misunderstood by the police officers themselves. The objective of this paper is basically to put down the police power as found under the Police Act and the relevant Shariah legislation.